Investigations into Dynamics and Levels of Fissile Radionuclide Accumulation in the Annual Tree Rings; The Problems of Biogeochemistry and Geochemical Ecology; № 1 (3) - Rikhvanov L. P. Leonid Petrovich; Arkhangelskaya T. A. Tatyana Aleksandrovna; Lukyanova E. V.; Nesvetaylo V. D. (2007, 2007)
В фонде НТБ ТПУ отсутствует